Wolfram Function Repository
Instant-use add-on functions for the Wolfram Language
Warning: This resource is provisional
Function Repository Resource:
Find a path that goes from one expression to another with a sequence of replacements
ResourceFunction["FindReplacePath"][theorem, axioms] finds a replacement path from the left-hand side of a theorem to its right-hand side using replacements specified by axioms. | |
ResourceFunction["FindReplacePath"][theorem,axioms,prop] return a specified property of a path. |
"ProofObject" | corresponding ProofObject |
"Path" | list of expressions constituting a found path (default) |
"Justification" | list of axioms used in each subsequent step of a path together with their orientations and positions |
"Rewrites" | list of rewriting functions that reproduce a path |
"PathTest" | test path endpoints to match a required statement |
"RewritesTest" | test-rewriting functions to successfully reproduce a path |
All | all of the above as an association |
Find a replacement path given a set of equations:
In[1]:= | ![]() |
Out[1]= | ![]() |
Find a replacement path using universally quantified equations:
In[2]:= | ![]() |
Out[2]= | ![]() |
In[3]:= | ![]() |
Out[3]= | ![]() |
In[4]:= | ![]() |
Out[4]= | ![]() |
In[5]:= | ![]() |
Out[5]= | ![]() |
In[6]:= | ![]() |
Out[6]= | ![]() |
Use names from AxiomaticTheory:
In[7]:= | ![]() |
Out[7]= | ![]() |
Use ProofObject to find a path:
In[8]:= | ![]() |
Out[8]= | ![]() |
In[9]:= | ![]() |
Out[9]= | ![]() |
Find a path in a string substitution system:
In[10]:= | ![]() |
Out[10]= | ![]() |
In[11]:= | ![]() |
Out[11]= | ![]() |
Find a path in a Wolfram model system:
In[12]:= | ![]() |
Out[12]= | ![]() |
In[13]:= | ![]() |
Out[13]= | ![]() |
Reproduce the found path using rewriting functions:
In[14]:= | ![]() |
Out[14]= | ![]() |
In[15]:= | ![]() |
Out[15]= | ![]() |
Degenerate axiom systems capable of deriving a==b-type statements can sometimes fail:
In[16]:= | ![]() |
Out[16]= | ![]() |
In[17]:= | ![]() |
Out[17]= | ![]() |
Test Boolean theorems:
In[18]:= | ![]() |
Out[18]= | ![]() |
NKS example:
In[19]:= | ![]() |
Out[19]= | ![]() |
In[20]:= | ![]() |
Out[20]= | ![]() |
This result is two steps shorter than the NKS path, but it uses the reverse of one axiom:
In[21]:= | ![]() |
Out[21]= | ![]() |
This work is licensed under a Creative Commons Attribution 4.0 International License